2019
DOI: 10.1063/1.5117163
|View full text |Cite
|
Sign up to set email alerts
|

Understanding enhanced mechanical stability of DNA in the presence of intercalated anticancer drug: Implications for DNA associated processes

Abstract: Most of the anticancer drugs bind to double-stranded DNA (dsDNA) by intercalative-binding mode. Although experimental studies have become available recently, a molecular-level understanding of the interactions between the drug and dsDNA that lead to the stability of the intercalated drug is lacking. Of particular interest are the modifications of the mechanical properties of dsDNA observed in experiments. The latter could affect many biological functions, such as DNA transcription and replication. Here we prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…The Parmbsc0 44 force field was selected for G-quadruplex nucleobases. Recent studies have reported that the Parmbsc0 is a valid force field for DNA simulations, [45][46][47] in particular for the simulations within the ns timescale. For atoms in the azobenzene, since it is a non-standard molecule, parameters were defined using the Generalized Amber Force Field (GAFF).…”
Section: Methodsmentioning
confidence: 99%
“…The Parmbsc0 44 force field was selected for G-quadruplex nucleobases. Recent studies have reported that the Parmbsc0 is a valid force field for DNA simulations, [45][46][47] in particular for the simulations within the ns timescale. For atoms in the azobenzene, since it is a non-standard molecule, parameters were defined using the Generalized Amber Force Field (GAFF).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, once dsDNA makes a complex with the positively charged histone octamer that partially neutralizes DNA backbone charges, both its bending and stretch modulus increase by almost four times [17 ]. Sahoo et al recently discovered that when drug molecules bind to dsDNA in the intercalation mode, the stretch modulus increases drastically, whereas the persistence length decreases similar to the scenario of dsDNA in monovalent salt solutions [15 ]. However, there exist conflicting reports in the literature claiming no change in DNA persistence length upon drug intercalation, as discussed in Refs.…”
Section: Dna In Different Environmentsmentioning
confidence: 99%
“…The design principle of a variety of drug molecules, including that for cancer and tumour treatments, is based on the principle that these molecules bind to DNA and make dsDNA melting extremely difficult, which thus could hamper the biological processes required for proper functioning of the cellular processes. In this context, Sahoo et al [15 ] employed steered molecular dynamics (MD) simulations of different pulling protocols to study the overstretching and melting transitions of dsDNA and found a significant increase in the dsDNA rupture force in the presence of intercalated drug molecules, which is due to the enhancement in the base-stacking interaction between adjacent base pairs present near to a drug intercalation site (Figure 3). This is in line with the recent revelation that the base-stacking interactions, instead of the previously thought base-pairing interactions, mostly contribute to the stability of dsDNA [59].…”
Section: Force-induced Dna Strand Separationmentioning
confidence: 99%
See 2 more Smart Citations